Tantangan Implementasi Net Zero Emission di Banten: Studi Kasus Pembangunan Geothermal Padarincang - Jatnika, Jajat; Amal, Mohamad Ilyasul (HK-Publishing, 2023)
AbstractThe Net Zero Emissions (NZE) program became a popular term after the Paris Climate Agreement was held in 2015. The program aims to reduce environmental pollution that has the potential to cause global warming. Energy is one of the sectors focused on achieving the NZ E program. Various countries have issued new regulations related to the supply of electrical energy that are adjusted to the NZE program. The regulation emphasizes replacing the operation of conventional power plants that use coal such as Steam Power Plants. The plant will later be removed and replaced with a New Renewable Energy (EBT) based power plant. However, various challenges and impacts will arise due to the shift from the use of fossil energy to EBT energy. This study aims to determine the challenges in carrying out the energy transition to achieve the NZE program. The narrative literature review method is used to analyze information and literature. The development of EBT generators is logically a priority step for Indonesia. This development is like increasing the co-firing composition by increasing the number of Geothermal Power Plants (PLTP) in Padarincang, Banten Province. The abundant availability of EBT in Indonesia is an opportunity that can be utilized optimally to achieve the NZE program.Keywords: International Environmental Institute, Environmental Issues, GlobalÂ AbstrakSetelah Perjanjian Paris Climate Agreement pada tahun 2015, inisiatif Net Zero Emissions (NZE) semakin populer. Tujuannya untuk mengurangi pencemaran lingkungan yang dapat menyebabkan pemanasan global. Salah satu sektor kunci yang menjadi sasaran program NZE adalah energi. Banyak negara telah memperkenalkan peraturan baru tentang pasokan listrik untuk menyelaraskan dengan program NZE. Peraturan ini memprioritaskan penggantian pembangkit listrik konvensional berbasis batubara seperti PLTU dengan pembangkit berbasis energi baru terbarukan (EBT). Namun, peralihan dari energi fosil ke energi EBT akan menimbulkan berbagai tantangan dan dampak. Studi ini bertujuan untuk mengidentifikasi tantangan yang terlibat dalam transisi ke energi EBT untuk mencapai program NZE. Pendekatan literature review naratif digunakan untuk menganalisis informasi dan literatur. Pengembangan pembangkit EBT merupakan langkah krusial bagii Indonesia. Salah satu cara untuk mencapainya adalah dengan menambah jumlah Pembangkit Listrik Tenaga Panas Bumi (PLTP) di Padarincang, Provinsi Banten. Sumber daya EBT Indonesia yang melimpah memberikan peluang untuk mencapai program NZE secara efisien.Kata Kunci: Net Zero Emission, Krisis Iklim, Pemanasan Global.